Biomarkers as a Prognostic Factor in COPD Exacerbation: A Cohort Study (2021)
ABSTRACT: The acute exacerbations of COPD (AECOPD) are one of the main causes of hospitalization and morbimortality in the adult population. There are not many tools available to predict the clinical course of these patients during exacerbations. Our goal was to estimate the clinical utility of C Reactive Protein (CRP), Mean Platelet Volume (MPV), eosinophil count and neutrophil/lymphocyte ratio (NLR) as in-hospital prognostic factors in patients with AECOPD. A prospective cohort study was conducted in patients who consulted three reference hospitals in the city of Medellın for AECOPD and who required hospitalization between 2017 and 2020. A multivariate analysis was performed to estimate the effect of biomarkers in the two primary outcomes: the composite outcome of in-hospital death and/or admission to the ICU and hospital length-of-stay. A total of 610 patients with a median age of 74 years were included; 15% were admitted to the ICU and 3.9% died in the hospital. In the multivariate analysis adjusted for confounding variables, the only marker significantly associated with the risk of dying or being admitted to the ICU was the NLR > 5 (OR: 3; CI95%: 1.5; 6). Similarly, the NLR > 5 was also associated to a lower probability of being discharged alive from the institution (SHR: 0.73; CI95%: 0.57; 0.94) and, therefore, a longer hospital stay. It was found that a neutrophil/lymphocyte ratio greater than 5 is a strong predictor of mortality or ICU admissions and a longer hospital stay in patients hospitalized with AECOPD.